Characteristics of Lichen Planus in Patients Attending a Tertiary Care Hospital in Bangladesh - Mahmud, Md. Mostaque; Khandker, Lubna; Hossain, Md. Shahadat; Rahman, Md. Mostafizur; Hossain, Mohammad Zaid (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 156-159 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15338